2015
DOI: 10.1007/978-3-319-18144-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2S Donors in Cancer Biology

Abstract: Hydrogen sulfide (H2S) donors including organosulfur compounds (OSC), inorganic sulfide salts, and synthetic compounds are useful tools in studies to elucidate the effects of H2S in cancer biology. Studies using such donors have shown the ability of H2S to suppress tumor growth both in vitro and in vivo, with some of them suggesting the selectivity of its cytotoxic effects to cancer cells. In addition to promoting cancer cell death, H2S donors were also found to inhibit cancer angiogenesis and metastasis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 80 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…To date, numerous H 2 S releasing drugs with different properties, donating mechanisms, and capabilities have been synthesized for experimental use. With the exception of their molecular targets, the anti-cancer effects of H 2 S donors have been extensively reviewed [26][27][28][29]. Herein, we will summarize recent findings on the roles of H 2 S donors in cancer management by illuminating their molecular targets, mechanisms involved and their downstream effects in cellular activities.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…To date, numerous H 2 S releasing drugs with different properties, donating mechanisms, and capabilities have been synthesized for experimental use. With the exception of their molecular targets, the anti-cancer effects of H 2 S donors have been extensively reviewed [26][27][28][29]. Herein, we will summarize recent findings on the roles of H 2 S donors in cancer management by illuminating their molecular targets, mechanisms involved and their downstream effects in cellular activities.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…These data further confirmed the roles of the CSE/H 2 S system in deacetylation of STAT3 via SIRT1 in promoting breast cancer progression, and indicated that I157172 promoted SIRT1-mediated deacetylation of STAT3 in breast cancer cells and consequently inhibited the growth of breast cancer cells. Discussion H 2 S serves important roles in cancer cells (8,9) alongside its physiological functions in normal somatic cells (27). The effects of exogenous H 2 S on cancer cells differ from those of endogenous H 2 S. Several H 2 S donors exert therapeutic effects on cancer cells (27), whereas endogenous H 2 S may promote the proliferation of some cancer cells (4,8,9).…”
Section: Cse/h 2 S System May Activate Stat3 Via the Downregulation Omentioning
confidence: 99%
“…Discussion H 2 S serves important roles in cancer cells (8,9) alongside its physiological functions in normal somatic cells (27). The effects of exogenous H 2 S on cancer cells differ from those of endogenous H 2 S. Several H 2 S donors exert therapeutic effects on cancer cells (27), whereas endogenous H 2 S may promote the proliferation of some cancer cells (4,8,9). CSE, which is an endogenous H 2 S synthase, is a pyridoxal-5'-phosphate-dependent enzyme that catalyzes L-cysteine to yield H 2 S (28,29).…”
Section: Cse/h 2 S System May Activate Stat3 Via the Downregulation Omentioning
confidence: 99%
“…In the liver, H 2 S can be catalyzed by both cystathionine b-synthase (CBS) and cystathionine g-lyase (CSE) (23). Accumulating studies have demonstrated that H 2 S is involved in the pathophysiological progression of tumors (24)(25)(26)(27). However, the potential mechanism of H 2 S in cancer is unclear and controversial.…”
Section: Introductionmentioning
confidence: 99%